2017
DOI: 10.2196/publichealth.7093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Viewing Smoking Scenes in Motion Pictures on Subsequent Smoking Desire in Audiences in South Korea

Abstract: BackgroundIn the modern era of heightened awareness of public health, smoking scenes in movies remain relatively free from public monitoring. The effect of smoking scenes in movies on the promotion of viewers’ smoking desire remains unknown.ObjectiveThe study aimed to explore whether exposure of adolescent smokers to images of smoking in fılms could stimulate smoking behavior.MethodsData were derived from a national Web-based sample survey of 748 Korean high-school students. Participants aged 16-18 years were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…In contrast to various findings that reported an association and causal relationship between smoking scenes in movies and smoking initiation among adolescents56 57as well as several human behavioural theories such as social learning theory58 and contextual effect theory,59 watching someone smoking might increase the likelihood of behavioural imitation followed by the instillation of a smoking-positive memory among viewers, which can influence future real-life behaviour 60. We did not find a significant association between being susceptible to smoking and watching someone smoking in a movie after adjusting for the confounding effect of other independent variables, which is in line with the finding by Polanska et al ,17 which showed no significant association between seeing someone smoking in a movie with SS.…”
Section: Discussionsupporting
confidence: 65%
“…In contrast to various findings that reported an association and causal relationship between smoking scenes in movies and smoking initiation among adolescents56 57as well as several human behavioural theories such as social learning theory58 and contextual effect theory,59 watching someone smoking might increase the likelihood of behavioural imitation followed by the instillation of a smoking-positive memory among viewers, which can influence future real-life behaviour 60. We did not find a significant association between being susceptible to smoking and watching someone smoking in a movie after adjusting for the confounding effect of other independent variables, which is in line with the finding by Polanska et al ,17 which showed no significant association between seeing someone smoking in a movie with SS.…”
Section: Discussionsupporting
confidence: 65%
“…An experimental study conducted in South Korea examined the role of contextual factors on smoking, such as smoking scenes in movies. 58) It was found that Korean adolescent males, in particular, were more likely to crave a cigarette after watching a smoking scene.…”
Section: Interventional Studiesmentioning
confidence: 99%
“…Environment is also an important factor that can promote and stimulate a person to smoke in different places, which increases the smoking rate 19,20 . Moreover, it is observed that advertisements promote smoking initiation among youth 21 .…”
Section: Resultsmentioning
confidence: 99%